2010
DOI: 10.1515/cclm.2010.124
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing serum total tryptase concentrations in a general adult population

Abstract: Serum total tryptase concentrations in adults are not significantly modified by atopy status, but may be modified by lifestyle factors, such as alcohol consumption and gender. Serum total tryptase concentrations are particularly dependent on age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
51
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 21 publications
9
51
4
Order By: Relevance
“…In our study, ST levels were higher in men than in women, in agreement with the study by Komarow et al [34] in atopic children and the Spanish study [15]. Alcohol consumption was negatively associated whereas smoking was positively associated with ST levels.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, ST levels were higher in men than in women, in agreement with the study by Komarow et al [34] in atopic children and the Spanish study [15]. Alcohol consumption was negatively associated whereas smoking was positively associated with ST levels.…”
Section: Discussionsupporting
confidence: 93%
“…This confirms the results of the Spanish population study [15] that found a tendency towards higher ST levels in obese persons and persons with the metabolic syndrome. The Spanish study included one third of the number of participants compared to the present study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this retrospective study, a slight but significant decrease of sBT levels (2.5%/year) over time was determined. In previous studies, sBT levels were reported to increase with age [42,43]. Investigators attributed a decrease in sBT levels, which is in contrast to the physiological process, to the effect of VIT.…”
Section: Discussionmentioning
confidence: 99%